Praktek Gadai Sawah di Kelurahan Klemunan Wlingi Blitar dalam Analisis Hukum Islam - Farah Diba Arafat; Farida Sekti Pahlevi (Jurnal Antologi Hukum, 2021)
In the Klemunan Village, Wlingi, Blitar, there is a practice of pawning with guaranteed fields that can be used indefinitely. This practice is detrimental to one of the parties because the income from Rahin is directly transferred to the Murtahin. The purpose of this study was to determine a precise analysis of Islamic law on the practice of pawning rice fields in the Klemunan, Wlingi, Blitar Villages and as a medium of knowledge for the surrounding community who still use the pawning method. Qualitative methods are used in this research, while field data collection uses interviews, documentation, and observation. Data analysis was done by the deductive method. This research shows that the rice field pawning contract in the Klemunan Village, Wlingi, Blitar is not by Islamic law, it is because when the contract takes place, the specific conditions must be met by Rahin so that the Murtahin can accept the rice fields. The contract is valid, but the conditions are considered void. According to Islamic legal theory, using the object of pawning the fields without a time limit is inappropriate because the Murtahin can use the object of the pawn without a time limit or until the debt is completed. In the Klemunan Village, the sub-district is not by Islamic law because when Rahin cannot pay its debt to the Murtahin, the rice fields used as collateral can change ownership to become the property of the Murtahin.